On the formation of desert loess. Issue 1 (July 2020) - Lancaster, Nicholas
Abstract: Sequences of quartz-rich coarse (20−63 μm) silt occur in many low- and midlatitude unglaciated arid and semiarid areas and have been termed "desert loess." The processes by which these deposits are generated have been debated for decades. All hypotheses to explain their origin seek to provide mechanisms for the generation of silt-sized material without glacial grinding, which is the main process involved in the production of coarse silt at high latitudes. Possible mechanisms for the formation of coarse silt in arid regions include derivation from preexisting siltstones, mechanical weathering of silicate rocks, and abrasion of sand grains in active dune environments during intense transport events. Examination of the characteristics of desert loess and field and laboratory experiments to assess the role of dune areas as a source of coarse silt by abrasion and/or resuspension of residual fines suggests that many loess sequences are dominated by locally derived coarse silt. Improvements in the characterization of desert loess particle size, mineralogy, and geochemistry are needed, however, to identify sources and sinks of coarse silt, especially when combined with climatic back-trajectory analysis. Properly scaled experiments and modeling of particle collisions will also help to better quantify the effectiveness of abrasion in the generation of coarse silt in support of field observations.